(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
Anti-discriminatory teacher education demands interconnected, reflective professionalization processes of both students and lecturers from multiple perspectives. To strengthen this, a pilot project at the University of X connected seminars of all teaching disciplines to professionalize students and lecturers within and outside their own seminars. The approach was evaluated by all parties involved. The project and initial reflections are presented in this article.